Restoration of Logged Humid Tropical Forests: An Experimental Programme at Harapan Rainforest, Indonesia. (March 2015) - Harrison, Rhett D; Swinfield, Tom
Restoration of degraded tropical forests can enhance ecosystem service provisioning, improve habitat quality for tropical forest biota and generate income from timber and NTFPs. In Indonesia alone, an estimated 25 million ha of former logging concessions are without current management, representing a huge opportunity for biodiversity conservation. However, currently such forests are typically converted to plantations. Realising the restoration potential of these forests will require viable business models that couple restoration goals with income generation. Unfortunately, understanding of natural succession trajectories and cost-effectiveness of restoration interventions remains poor. We present an overview of research, including three planned experiments designed to test the economic viability of large-scale restoration treatments, in a former logging concession at Harapan Rainforest (98, 455 ha), Indonesia. These experiments will address the following questions: (1) Can the selective removal of pioneer trees, including an invasive species, be used to accelerate succession; (2) how does the functional diversity of the planted matrix affect growth and survival of a high value target species; and (3) how does seed density affect recruitment success in direct seeding treatments? Treatments will be applied to large compartments (4 8 ha) to reduce edge effects and simplify management. Monitoring plots (20 × 20 m × 5 reps) within each compartment will be used to assess silvicultural responses, while changes in biodiversity and carbon storage will be monitored at the compartment level. The large spatial scale and high replication of the treatments will establish an experimental platform that will inform many different aspects of tropical forest ecology.